High‐Frequency Ultrasound Boosts Bull and Human Sperm Motility. Issue 11 (9th February 2022) - Gai, Junyang; Dervisevic, Esma; Devendran, Citsabehsan; Cadarso, Victor J.; O'Bryan, Moira K.; Nosrati, Reza; Neild, Adrian
Abstract: Sperm motility is a significant predictor of male fertility potential and is directly linked to fertilization success in both natural and some forms of assisted reproduction. Sperm motility can be impaired by both genetic and environmental factors, with asthenozoospermia being a common clinical presentation. Moreover, in the setting of assisted reproductive technology clinics, there is a distinct absence of effective and noninvasive technology to increase sperm motility without detriment to the sperm cells. Here, a new method is presented to boost sperm motility by increasing the intracellular rate of metabolic activity using high frequency ultrasound. An increase of 34% in curvilinear velocity (VCL), 10% in linearity, and 32% in the number of motile sperm cells is shown by rendering immotile sperm motile, after just 20 s exposure. A similar effect with an increase of 15% in VCL treating human sperm with the same setting is also identified. This cell level mechanotherapy approach causes no significant change in cell viability or DNA fragmentation index, and, as such, has the potential to be applied to encourage natural fertilization or less invasive treatment choices such as in vitro fertilization rather than intracytoplasmic injection. Abstract : Sperm motility plays a central role in both natural fertilization and clinical sperm selection as the key male fertility parameter. However, there is an absence of methods to improve sperm motility without introducing more damage. Here, it is found that treating sperm cells with high frequency ultrasound results in a boost in sperm motility by enhancing sperm metabolism.